If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = 21 + -2x Reorder the terms: 3 + 4x = 21 + -2x Solving 3 + 4x = 21 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 4x + 2x = 21 + -2x + 2x Combine like terms: 4x + 2x = 6x 3 + 6x = 21 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 6x = 21 + 0 3 + 6x = 21 Add '-3' to each side of the equation. 3 + -3 + 6x = 21 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 21 + -3 6x = 21 + -3 Combine like terms: 21 + -3 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| x*x-3-6x=0 | | -2(1+8)=x | | 4x-4=80 | | 6(x-4)=-2(x+8) | | 10x*8y=960 | | 10+8a=11a-6 | | (x^2+x-4)=0 | | 8x+4y=40 | | 1/2(18x-8)=6x-7/3 | | 6(3-x)-5(2x-4)=4(3x-1)+14 | | 10m=96 | | 2m+5=20-3m | | 7x-5=61 | | 15x+40=175 | | 7x-3=15+x | | 1200=s^2+6s | | x^2+5x-22=0 | | x+72=138 | | 16cos^4x=0 | | 9p-1=2 | | (7x-2)(11x-34)= | | 3r(2r+7)-(r-4)= | | 139-3X=5X+9 | | 4X^2+4X+2=0 | | 5p+28=12p | | 3x+2(7x-13)=-162 | | 240=-7x-3(4x-23) | | 7x^2+xy+y^2=9 | | 2x+5y=29 | | 5x-4(7x+23)=184 | | 5x-(7-2x)=8x+9 | | 2y-8=30 |